Feasibility, effectiveness and acceptability of two perturbation-based treadmill training protocols to improve reactive balance in fall-prone older adults (FEATURE): protocol for a pilot randomised controlled trial - Hezel, Natalie; Sloot, Lizeth H.; Wanner, Philipp; Becker, Clemens; Bauer, Jürgen M.; Steib, Simon; Werner, Christian (BMJ open, 2023)
Introduction: Perturbation-based balance training (PBT) targets the mechanism of falls (eg, slipping, tripping) to specifically train the recovery actions needed to avoid a fall. This task-specific training has shown great promise as an effective and efficient intervention for fall prevention in older adults. However, knowledge about the dose-response relationship of PBT, as well as its feasibility and acceptability in older adults with increased risk of falling is still limited. Thus, the aim of this study is to compare the effectiveness of two different treadmill PBT protocols for improving reactive balance control in fall-prone older adults, and to evaluate the feasibility and acceptability of these protocols. - Methods and analysis The study is designed as a pilot randomised controlled trial with a 6-week intervention and 6-week follow-up period. Thirty-six community-dwelling, fall-prone (Timed Up and Go >12 s, habitual gait speed <1.0 m/s and/or fall history) older adults will be randomised (1:1) to receive six (weeks 1-6) or two treadmill PBT sessions (weeks 1+6) plus four conventional treadmill training sessions (weeks 2-5). Training sessions are conducted 1×/week for 30 min. Each PBT will include 40 perturbations in anterior-posterior and mediolateral directions. Reactive balance after perturbations in standing (Stepping Threshold Test (STT)) and walking (Dynamic Stepping Threshold Test (DSTT)) will be assessed as the primary outcome for effectiveness. Secondary outcomes are spatiotemporal and kinematic parameters collected during STT, DSTT and PBT, maximum perturbation magnitude for each PBT session, static and dynamic balance, physical capacity, physical activity, concerns with falling and executive functions. Feasibility will be assessed via training adherence, drop-out rate, perturbations actually performed and adverse events; and acceptability via self-designed questionnaire and focus groups. - Ethics and dissemination The study has been approved by the Ethics Committee of the Medical Faculty Heidelberg (S-602/2022). Findings will be disseminated through publications in peer-reviewed journals and conference presentations. - Trial registration number DRKS00030805.